EFFECT OF WORK DISCIPLINE, WORKLOAD, AND CAREER DEVELOPMENT ON EMPLOYEE PERFORMANCE - Ervin Nora Susanti; Firman Jaya; Herni Widiyah Nasrul; Zulkifli Zulkifli; Widodo Ismanto (International Conference on Business Management and Accounting, 2022)
This study aims to anlayze the effect of work discipline, workload, and career development on employee performance partially and simultaneously. This research uses quantitative methods and uses a questionnaire with a Likert scale. The population of this research is 100 employees of PT Citra Buana Prakarsa. Samples were taken using the census method. Data were analyzed using multiple linear regression analysis and hypothesis testing using partial t test and simultaneous F test. The results show that: (1) Work Discipline partially has a significant effect on employee performance. (2) Workload partially has a significant effect on employee performance, (3) Career development partially has a significant effect on employee performance, and (4) simultaneously work discipline, workload, and career development have a significant effect on employee performance.